A Comparison between the Chemical and Physical Aspects of Sawa Lake Water which is Located Western Samawah City (Iraq), and the Aspects of some Wells Water which are Located around the Lake - Taha Yaseen Farhan; Athier Hussin (Engineering and Technology Journal, 2016)
This research included a comparison between the chemical and physical aspects of Sawa Lake water and the chemical and physical aspects of wells water, which are located around Sawa Lake. This research has chosen four wells that are located near Sawa Lake and then the laboratory tests were done for the samples of wells water and Sawa Lake water a long three months (November, December and January 2014-2015). The results showed, there are large differences between the chemical and physical aspects of wells water, in comparison with the chemical and physical aspects of Sawa Lake water. The high concentration of salinity for the water of Sawa Lake and the differences of temperature between the water of Sawa Lake and wells was the distinguishing feature. The average temperature for well (1) water was (24.5ºC) whereas for Sawa Lake was (12ºC). In addition, the average of electrical Conductivity for Sawa Lake water was (37600µs/cm) whereas for well (1) was (5244µs/cm) and well (4) (5730µs/cm). In addition, there were very large differences in the Chloride concentrations between the Sawa lake water (8987 mg/L), the water of first well (993.3 mg/L) and the water of second well (1135 mg/L).